Employee Job Satisfaction a Case Study in a Building Materials Business - Silvana Syah; Faisal Hamdi; Bambang Jati Sentot; Ruland Jack Sumampouw; Iskandar Ahmaddien (Budapest International Research and Critics University, 2022)
The goal of the study is to: 1. Knowing the impact on employee job satisfaction Building Materials Business at Ukui, 2. Knowing the effect of work culture on workers satisfaction Building Materials Business at Ukui, 3. Knowing the effect of motivation on workers satisfaction Building Materials Business at Ukui, 4. To find out the effect of leadership, work culture and work motivation simultaneously on job satisfaction of workers of Building Materials Business at Ukui. The method of data analysis is data processing using statistical calculations. Researchers collect data and then determine the tools to obtain data from the elements to be collected. The tool used in this research is a questionnaire. Using the multiple linear regression statistical analysis approach. The findings of this study are as follows: 1. Leadership has no effect on worker job satisfaction as argument by the leadership importance value greater than 0.05, namely 0.064 with a t-count value of -1.882 <ttable 1.993. 2. Work culture has no effect on workers’ satisfaction as evidenced by the leadership significance value greater than 0.05, namely 0.321 with a t-count value of 0.998 <t-count 1.993. 3. Work motivation has an effect on job satisfaction as evidenced by the leadership significance value less than 0.05, namely 0.000 with a t-count value of 6.095 > t-count 1,993.4. Leadership, work culture, and motivation to work together have an effect on workers satisfaction as evidenced by the value of Fcount > Ftable which is 18,095 > 2.72 and the significance stage of 0.000 is much smaller than the significant level of 0.05. The value of the coefficient of determination (Adjusted R Square) of 0.403 or 40.3% of variance in employee job satisfaction can be described by variance of the three independent variables. Suggestions for further research, to further expand the factors that affect employee job satisfaction. Further research can add variables such as work communication, work support facilities, work discipline, etc.